INFLUÊNCIA INDIVIDUAL DE TOUROS NA PRODUÇÃO IN VITRO DE EMBRIÕES - SILVA, Rafaela Lira Dos Santos; ORUÊ, Andrey Makálister Souza; RIBEIRO, Cláudio Luiz Ferreira; RIBEIRO Mariane Ferreira; OLIVEIRA, Arianny Lima Ferreira; MELO STERZA, Fabiana de Andrade (ANAIS DO ENIC, 2025)
-